Reversible acute myocardial injury following air bag deployment. Issue 5 (20th April 2005) - Nagarajan, D V; Wilde, M; Papouchado, M
Abstract : This case report is about a 62 year old woman who was involved in an accident while driving her car, during which the driver side air bag deployed. She experienced intense anterior chest pain that radiated to her left arm after the accident, but was otherwise well; there was no significant medical history. An electrocardiogram done one and half hours after admission revealed 1 mm ST segment elevation in leads V2 and V3 and troponin 1 level was raised. She underwent cardiac catheterisation but three months after the accident both ECG and echocardiographic studies were normal. It is suggested that she underwent cardiac contusion rather than a myocardial infarction.